A Large Trolling Lure Shank from Ahuahu Great Mercury Island, New Zealand - Furey, Louise; Phillipps, Rebecca; Emmitt, Joshua; McAlister, Andrew; Holdaway, Simon (Waka Kuaka, 2020)
Large stone trolling lure shanks, greater than 100 mm, are rare and stylistically associated with the early period of Māori occupation of Aotearoa New Zealand. The triangular-sectioned shank is distinctive and reminiscent of Polynesian forms. The 2016 find during excavations at T10/360 at Waitapu in Coralie Bay, Ahuahu Great Mercury Island, is the first to be recovered in an archaeological context and only the third large shank attributed to the North Island. Moreover, the shank is the largest complete example known. Radiocarbon dates from contexts in direct association with the shank indicate deposition in the early 15th century, slightly later than other sites such as Wairau Bar and Shag River Mouth where similar shanks have been found. A comparative analysis of the attributes of all 28 shanks in New Zealand museum collections indicates no regional patterns are evident. We review the context in which the Ahuahu shank was found, and its importance, along with the other items recovered, for the interpretation of the Waitapu occupation. We also consider the various reported interpretations of large trolling shanks and, based on Polynesian examples where symbolism and function are discussed, suggest large shanks were not used directly in fishing but had a fishing-related role.